DEVELOPMENT OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN UZBEKISTAN (Conference Zone, 2021)
The article examines the role of small business and private entrepreneurship in the development of Uzbekistan, its development trends across sectors